Fabrication of alginate scaffold with tunable properties and geometry - Lee, Siew Cheng. (2013)
Tissue engineering has gained extensive interest as a great potential for regeneration and repair of diseased tissues, thus motivating researchers in the biomedical field into the development of scaffolds for tissue engineering. Due to the biocompatibility of hydrogels and its ability to mimic extracellular matrix (ECM), they have been considered as the emerging candidate for tissue scaffolds engineering. Development of three-dimensional (3-D) scaffolds for replacement of functional tissues is essential as they act as an optimum microenvironment for tissue growth and regeneration. [1, 2] The principle goal of 3-D scaffolds is to mimic nature’s own scaffold (ECM) to allow cells to work as they would in-vivo even in a simulated environment. The architecture of scaffolds has been intensively studied as it is vital for vascularisation and the transport of nutrients for the developing tissue. Hence, 3-D scaffolds should incorporate features such as a network of interconnected pores and a well controlled pore sizes and shapes. In this research, it is aimed at conducting a study on the tunable properties of alginate scaffold of different geometries using cross-linking process. Calcium D-gluconate was employed as the cross-linking agent to form hydrogel with 2% (w/v) alginate solution. Using moulds of desired shapes, 3-D scaffolds were successfully fabricated by freeze-drying. Morphological information, mechanical properties, thermal properties and swelling profile of the hydrogels were characterized by a series of tests. The influences of cross-linking concentrations and gelation time were studied. Post-fabrication treatment was also used and characterized in order to strengthen the hydrogels formed. The results obtained concerning the influence of various factors on the properties of scaffold would form the basis and rational to continue research on fabricating 3-D scaffolds for specific applications.